PENERAPAN AWIG-AWIG DESA ADAT BLAHKIUH TERHADAP BHAYA LAN DUSTA DI DESA ADAT BLAHKIUH, KABUPATEN BADUNG - Putra, I Made Wisnata; Sutrisni , Ni Komang (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
Indigenous peoples are groups of people who have ancestral origins from generation to generation in certain geological areas and have their own system of values, ideology, economy, culture, politics, and territory. Based on Bali Provincial Regulation No. 4 of 2019 concerning Customary Villages in Bali where it is explained that customary villages themselves have the authority to regulate their own territorial autonomy. Thus, Traditional Villages in Bali have their own authority, and the rules of each customary village in Bali are certainly different according to the village, kala, patra which means place, time, identity/situation. The rules in each Traditional Village in Bali are called Awig awig. Awig-awig is a customary village rule made by indigenous people, Awig-awig contains basic rules related to customary territory, customary village customs, religion and sanctions. Blahkiuh Traditional Village has legal rules in the form of awig-awig of blahkiuh traditional village where in the awig-awig of blahkiuh traditional village contains the rules of indik bhaya and lie.